IMPROVING STUDENTS’ READING COMPREHENSION OF VIIIGRADE AT SMPN 4 TOLITOLI UTARA THROUGH SUMMARY TECHNIQUE - H, Ismail Yunus (Universitas Madako Tolitoli, 2017)
The objective of this research was to identify whether the use of summary technique effective to improve students’ ability in reading comprehension. An experimental design was used to collect the data, while quantitative approach was used to analyze them. The study was taken by the first grade of SMP Negeri 4 Tolitoli Utara. It was conducted in one class (VIII). The data were obtained through a pre-test and post-test. The pre-test was used to measure the students’ previous ability in reading comprehension, the treatments were applying materials through summary technique, and the post-test was used to find out the students’ reading ability after given treatments.The result of the analysis showed that summary technique contribute greatly to the students in reading comprehensio. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test was 46,38 while in the post-test improved up to 78,13. Moreover the Minimum Mastery Criterion of English lesson was 75 (seventy-five). Then the data of both test were analyzed by using T-test, and the result showed that the T-tes value 2,229 was greater than T-table value -14,246. It can be inferred that summary technique was very effective to improve students’ ability in reading comprehension. Key words: Summary technique, teaching reading, narative text